2017
DOI: 10.1002/cjce.23023
|View full text |Cite
|
Sign up to set email alerts
|

Wettability alteration of reservoir rocks to gas wetting condition: A comparative study

Abstract: Productivity of gas condensate reservoirs reduces significantly due to the near wellbore condensate/water blockage phenomenon. A novel, permanent solution to alleviate this problem is near wellbore wettability alteration of reservoir rocks to preferentially gas wetting conditions; industrial chemical materials are good candidates for this purpose, because of their eco‐friendly characteristics, economical price, and mass production. In this paper, a comparative study is conducted on two industrial fluorinated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In the recent decade, it was demonstrated that some chemical agents could change the rock surface wettability (Dehghan Monfared et al 2016;Azadi Tabar et al 2019a;Arabloo et al 2016;Erfani Gahrooei et al 2017;Gahrooei and Ghazanfari 2017a, b;Maghzi et al 2011Maghzi et al ,2012Mohammadi et al 2012;Gahrooei et al 2017;Sadatshojaei et al 2016;Roustaei et al 2013). Usually, chemical consolidator/stabilizer agents could be adsorbed or glued onto the surface of reservoir rock, and such phenomena might change the inherent wettability of the treated region (around the wellbore) (El-Hoshoudy et al 2017;Failed 2017).…”
Section: Wettability Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent decade, it was demonstrated that some chemical agents could change the rock surface wettability (Dehghan Monfared et al 2016;Azadi Tabar et al 2019a;Arabloo et al 2016;Erfani Gahrooei et al 2017;Gahrooei and Ghazanfari 2017a, b;Maghzi et al 2011Maghzi et al ,2012Mohammadi et al 2012;Gahrooei et al 2017;Sadatshojaei et al 2016;Roustaei et al 2013). Usually, chemical consolidator/stabilizer agents could be adsorbed or glued onto the surface of reservoir rock, and such phenomena might change the inherent wettability of the treated region (around the wellbore) (El-Hoshoudy et al 2017;Failed 2017).…”
Section: Wettability Variationmentioning
confidence: 99%
“…Well productivity of oil and gas reservoirs can be severely impaired by wettability variation around the wellbore. For example, in gas condensate reservoirs, many studies focused on modification of phase mobility by wettability alteration to gas-wet around wellbore (Erfani Gahrooei et al 2017;Gahrooei and Ghazanfari 2017a, b;Gahrooei et al 2017;Azadi Tabar et al 2019c). Typically, these reservoirs are initially single-phase gas, but after pressure decline below the dew point pressure because of gas production, a trapped condensate liquid phase by capillary forces is formed (Aminnaji et al 2015).…”
Section: Future Studiesmentioning
confidence: 99%
“…Recently, nanoparticles were used to alter the rock wettability for both carbonate and sandstone formations [37,[42][43][44][45][46]. Aminnaji et al [42] and Erfani Gahrooei et al [43] found that nanofluid can considerably change the wettability of carbonate and sandstone rocks to preferentially gas wet by aging the rocks for around one day. They mentioned that the gas wetting surface could be achieved by increasing the surface roughness and decreasing surface free energy.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms are proposed to explain the incremental oil recovery associated with MEOR, among which are the reduction in the oil-water IFT and changes in the wettability of the system and selective plugging mechanism [10][11][12][13]. Numerous experimental and numerical studies have been conducted to understand the impact of wettability alteration and IFT reduction [14][15][16][17][18][19][20][21][22][23][24]. Kowalewski et al [25] showed that the bacterial growth could both reduce IFT and alter the wettability state toward less oil-wet conditions.…”
Section: Introductionmentioning
confidence: 99%